The DNA load of six high-risk human papillomavirus types and its association with cervical lesions (2015)
Background: Analysing human papillomavirus (HPV) viral load is important in determining the risk of developing cervical cancer (CC); most knowledge to date regarding HPV viral load and cervical lesions has been related to HPV-16. This study evaluated the association between the viral load of the six most prevalent high-risk viral types in Colombia and cervical intraepithelial neoplasia (CIN) frequency. Methods: 114 women without CIN and 59 women having CIN confirmed by colposcopy, all of them positive by conventional PCR for HPV infection in the initial screening, were included in the study. Samples were tested for six high-risk HPV types to determine viral copy number by real-time PCR. Crude and adjusted odds ratios (ORa) were estimated for evaluating the association between each viral type's DNA load and the risk of cervical lesions occurring. Results: The highest viral loads were identified for HPV-33 in CIN patients and for HPV-31 in patients without lesions (9.33 HPV copies, 2.95 interquartile range (IQR); 9.41 HPV copies, 2.58 IQR). Lesions were more frequent in HPV-16 patients having a low viral load (3.53 ORa, 1.16-10.74 95%CI) compared to those having high HPV-16 load (2.62 ORa, 1.08-6.35 95%CI). High viral load in HPV-31 patients was associated with lower CIN frequency (0.34 ORa, 0.15-0.78 95%CI). Conclusions: An association between HPV DNA load and CIN frequency was seen to be type-specific and may have depended on the duration of infection. This analysis has provided information for understanding the effect of HPV DNA load on cervical lesion development. © 2015 applies to the data made available in this article, unless otherwise stated.